PENERAPAN TIRAI REL ELEKTRIK UNTUK OPTIMALISASI PEMISAHAN SHAF ANTARA LAKI-LAKI DAN PEREMPUAN DI MASJID AL-IKHLAS DESA SRIWIJAYA - Sari, Nirmala; Ari Fahril, Muhammad; Naziah, Afrahun; Gempa, Muhammad (Fakultas Teknik, Universitas Samudra, 2024)
A curtain separating the rows of women and men is a common feature found in some mosques or prayer rooms where women and men are separated during prayer. This is done to maintain privacy and prevent unwanted interactions during prayer times. The divider can be a curtain, partition, or wall that separates the prayer areas for men and women. Understanding that the use of a row divider between women and men is usually done manually by sliding the curtain when needed, by introducing an automatic divider using an electric rail curtain, this process can be made easier and more efficient. Automatic dividers can help save time by eliminating the need to manually slide the curtain. This is especially useful when opening or closing the row divider quickly for activities or lectures taking place in the mosque. It can also be a step towards the use of more modern technology in the setting of mosques and other places of worship.